Subcutaneous panniculitis-like T-Cell lymphoma in a child presenting as an abdominal wall mass - Anjana Bairagi; Morag Whyte; Roy Kimble (Elsevier, 2020)
Childhood panniculitides are not common. Histopathological diagnostic approach is vital to differentiate this group of pathologies that commonly present with inflammation of the subcutaneous adipose tissue. Pediatric subcutaneous panniculitis-like T-cell lymphomas are rare. Treatment modalities include observation, surgical excision, radiotherapy, immunosuppression, and chemotherapy. The case of an 18-month female who presented with a flank mass that was diagnosed as a subcutaneous panniculitis-like T-cell lymphoma and successfully managed with intensity-reduced, dual agent immunosuppression is described.